Building Resilience Against Disinformation : Need for Wider Education - Neubronner, Stephanie (2018)
Increasingly, cyber threats have been directed at targets with economic, political and social impact with the aim of sowing confusion, fraying civic threads, and intensifying existing polarisations. Singapore needs to commit towards instructing the wider public on how to manage disinformation campaigns.